2022
DOI: 10.1111/jth.15589
|View full text |Cite
|
Sign up to set email alerts
|

Major bleeding during oral anticoagulant therapy associated with factor V activation by factor Xa

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…They concluded that factor Xa-mediated activation of factor V represents a specific thrombin generation activation pathway during coagulation initiation, a process that may be particularly important among anticoagulated patients with major bleeding. 32 Taken together, these findings suggest that correcting kinetic TGA parameters, in addition to quantitative parameters, may be relevant with respect to predicting a meaningful hemostatic effect. The mean LT in plasma from healthy volunteers ranges from 1.9 to 2.3 minutes when measured using CAT.…”
Section: Study Methodsmentioning
confidence: 75%
“…They concluded that factor Xa-mediated activation of factor V represents a specific thrombin generation activation pathway during coagulation initiation, a process that may be particularly important among anticoagulated patients with major bleeding. 32 Taken together, these findings suggest that correcting kinetic TGA parameters, in addition to quantitative parameters, may be relevant with respect to predicting a meaningful hemostatic effect. The mean LT in plasma from healthy volunteers ranges from 1.9 to 2.3 minutes when measured using CAT.…”
Section: Study Methodsmentioning
confidence: 75%
“…The other intrinsic process involves a membrane-bound tenase complex composed of factor IXa, its cofactor factor VIIIa, and calcium ions activating factor X on the platelet surface. Factor Xa then triggers prothrombin to thrombin, resulting in blood coagulation [140]. A Factor X homolog was revealed to cleave the viral S protein at the S1/S2 boundary, allowing the virus to enter host cells [141].…”
Section: Factor Xamentioning
confidence: 99%